- #1

yungman

- 5,742

- 290

I need to convert[tex]x^{2}y''+2xy'+[kx^{2}-n(n+1)]y=0[/tex] using [tex]y=x^{-\frac{1}{2}}w[/tex] to a normal Modified Bessel Equation and I cannot get to that. I check many times and I must be having a blind spot!

This is my work:

[tex]y=x^{-\frac{1}{2}} w \Rightarrow y'=-\frac{1}{2}x^{-\frac{3}{2}}w+x^{-\frac{1}{2}}w' \Rightarrow y''=\frac{3}{4}x^{-\frac{5}{2}}w-\frac{1}{2}x^{-\frac{3}{2}}w'+x^{-\frac{1}{2}}w''-\frac{1}{2}x^{-\frac{3}{2}}w'[/tex]

[tex]x^{2}y''+2xy'+(kx^{2}-n(n+1))y=0 \Rightarrow[/tex]

[tex] [\frac{3}{4}x^{-\frac{1}{2}}w-\frac{1}{2}x^{\frac{1}{2}}w'+x^{\frac{3}{2}}w''-\frac{1}{2}x^{\frac{1}{2}}w']+[2x^{\frac{1}{2}}w'-x^{-\frac{1}{2}}w]+[kx^{\frac{3}{2}}w-n(n+1)x^{-\frac{1}{2}})w]=0[/tex]

Grouping w'', w' and w terms:

[tex]x^{\frac{3}{2}}w''+(-x^{\frac{1}{2}}+2x^{\frac{1}{2}})w'+(\frac{3}{4}x^{-\frac{1}{2}}-x^{-\frac{1}{2}}+kx^{\frac{3}{2}}-n(n+1)x^{-\frac{1}{2}})w=0[/tex]

Multiply by [tex]x^{\frac{1}{2}}[/tex] This give:

[tex]x^{2}w''+xw'+(\frac{3}{4}-1+kx^{2}-n(n+1))w=0[/tex]

I can't get the standard Modified Bessel equation because the 3/4-1 in the w term cannot be cancel out.

Please tell me what I did wrong.

Thanks

Alan

This is my work:

[tex]y=x^{-\frac{1}{2}} w \Rightarrow y'=-\frac{1}{2}x^{-\frac{3}{2}}w+x^{-\frac{1}{2}}w' \Rightarrow y''=\frac{3}{4}x^{-\frac{5}{2}}w-\frac{1}{2}x^{-\frac{3}{2}}w'+x^{-\frac{1}{2}}w''-\frac{1}{2}x^{-\frac{3}{2}}w'[/tex]

[tex]x^{2}y''+2xy'+(kx^{2}-n(n+1))y=0 \Rightarrow[/tex]

[tex] [\frac{3}{4}x^{-\frac{1}{2}}w-\frac{1}{2}x^{\frac{1}{2}}w'+x^{\frac{3}{2}}w''-\frac{1}{2}x^{\frac{1}{2}}w']+[2x^{\frac{1}{2}}w'-x^{-\frac{1}{2}}w]+[kx^{\frac{3}{2}}w-n(n+1)x^{-\frac{1}{2}})w]=0[/tex]

Grouping w'', w' and w terms:

[tex]x^{\frac{3}{2}}w''+(-x^{\frac{1}{2}}+2x^{\frac{1}{2}})w'+(\frac{3}{4}x^{-\frac{1}{2}}-x^{-\frac{1}{2}}+kx^{\frac{3}{2}}-n(n+1)x^{-\frac{1}{2}})w=0[/tex]

Multiply by [tex]x^{\frac{1}{2}}[/tex] This give:

[tex]x^{2}w''+xw'+(\frac{3}{4}-1+kx^{2}-n(n+1))w=0[/tex]

I can't get the standard Modified Bessel equation because the 3/4-1 in the w term cannot be cancel out.

Please tell me what I did wrong.

Thanks

Alan

Last edited: